Activation and function of mucosal gamma delta T cells - Misiak, Alicja (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
γδ T cells are innate-like lymphocytes characterised by rapid activation following infection or tissue injury. They are enriched in the skin and epitheliae of various organs, where breach of the barrier is likely to occur. γδ T cells appear to segregate into functional subsets according to the TCR they express and cells with specific VγVδ combinations preferentially home to particular sites in the body. While a lot is known about peripheral γδ T cells, very little work has been done on tissue resident γδ T cells, which are more likely to play a role in the initiation phase of the immune response.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin